PENERAPAN STRATEGI BELAJAR PETA KONSEP (CONCEPT MAPPING) UNTUK MENINGKATKAN HASIL BELAJAR PKN SISWA KELAS IV SEKOLAH DASAR - Asril (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2018)
This research is motivated by the lack of a student learning outcomes can be seen from the results of four grade students studied 72 Harapan Baru Elementary School, with an average value of 68. Therefore, the researchers provide an alternative to the application of the concept map learning strategy in the fourth grade 72 Harapan Baru. This research aims to improve learning outcomes PKn Elementary School four grade students Mandau sub 72 Harapan Baru with learning Implementation Strategy Concept Maps. This research is a form of classroom action research (PTK) with 2 cycles. Based on research data anlisis after implementing learning strategies Concept Map, the average percentage of the activity of teachers in the first cycle 66,66% increased to 87,46% in the second cycle. The average percentage of student activity also increased, namely 56,25% in the first cycle increased to 83,33% in the second cycle. Student learning outcomes in basic score by the average value of 68 and the first cycle increased with an average value of 71,25 class with an increasing percentage of learning outcomes 4,77% and the percentage of students who completed 65%, and the second cycle increased again by an average of 75.50 with the percentage improvement class learning outcomes 11,02% and the percentage of students who completed 80%. These results indicate that the application of learning strategies concept maps can enhance learning outcomes PKn four grade students of SD Negeri 72 Harapan Baru.